Diagnosis and Management of Renal Anemia in Stage 5 Chronic Kidney Disease Patients on Hemodialysis - Luh Dwi Briliantari Libriana; Bhanu Kumar (Syntax Corporation, 2026)
Chronic Kidney Disease (CKD) is a degenerative disease characterized by a decline in renal function due to structural or functional abnormalities persisting for more than three months. The causes of CKD are varied and can be categorized into three major groups: prerenal, intrarenal, and postrenal causes. The pathogenesis of CKD is characterized by a decrease in the number of functional nephrons, leading to decompensation of renal function. CKD can result in various conditions, such as fluid and sodium retention, metabolic acidosis, hyperkalemia, hyperphosphatemia, and anemia. Several types of anemia may occur in patients with CKD, including iron deficiency anemia, anemia of chronic disease, anemia due to erythropoietin deficiency, or mixed-type anemia. Several diagnostic methods can be used to identify anemia in CKD, such as a complete blood count, peripheral blood smear morphology, absolute reticulocyte count, erythropoietin (EPO) levels, and iron status evaluation. The treatment of anemia in CKD patients undergoing hemodialysis aims to improve quality of life, reduce the need for blood transfusions, improve cognitive function, and decrease morbidity and mortality. Management of anemia in CKD requires various considerations, including the use of oral or intravenous iron supplementation, erythropoietin injections, and blood transfusions if previous therapies fail to achieve the target hemoglobin levels. The therapeutic target for CKD patients with anemia is to increase hemoglobin (Hb) levels to a maximum of 11.5 g/dL, as this target is considered capable of reducing mortality among CKD patients with anemia.